PEMILIHAN SUPPLIER TEBU MENGGUNAKAN INTEGRASI AHP-TOPSIS PADA AGROINDUSTRI TEBU - Zahira, Nabila Fairuza; Pulansari, Farida (Jurnal Teknologi Industri Pertanian, 2023)
Business competition is getting tougher, making business idea owners vying to produce high quality products. One aspect that determines the quality of the products produced is the selection of manufacturing raw materials. The objective of this study was to identify the most suitable sugarcane suppliers with a set of criteria and sub-criteria. Supplier evaluation is required for the acquisition of sugarcane raw materials. Geographical factors, quality, performance history, impression, capacity, and delivery are all taken into account as evaluation criteria. In this study, AHP (Analytical Hierarchy Process) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) were used to determine the order of preference of sugarcane suppliers, with AHP assigning different probability values to each criterion and TOPSIS directing customers towards the most reliable supplier. Supplier 1 has a preference value of 0.5038, Supplier 2 has a value of 0.4258, Supplier 3 has a value of 0.2931, Supplier 4 has a value of 0.5686, and Supplier 5 has a value of 0.1715. This study used a total of six characteristics and the most influential of which is quality. Keywords: AHP, sugarcane, supplier selection, TOPSIS